ANALISIS PENGARUH HARGA KOMPETITIF, WORD OF MOUTH DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN COKELAT SULAMINA DI KEPULAUAN SULA MALUKU UTARA (Studi Kasus: Pabrik Sulamina) - Yainahu, Nur Mala; Pelupessy, Merry Margareth; Ayunani, Faras Zulina; Saununu, Siska Jeanete (Manis: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of competitive price word of mouth and brand image on the purchase decision of Sulamina Chocolate in the Sula Islands Regency (Sanana), North Maluku. Sulamina Chocolate is a local cocoa-based product that has become known as a regional specialty souvenir. This research applies a quantitative approach using a survey method by distributing questionnaires to 100 respondents who have purchased the product. Data analysis was conducted using multiple linear regression assisted by SPSS software. The results show that price has a positive and significant influence on purchasing decisions, with a significance value of 0.034. Word of mouth is the most dominant factor, with a significance value of 0.000 and the highest regression coefficient (0.641). Brand image also shows a positive and significant influence with a significance value of 0.044. Together, these three variables contribute to the purchasing decisions of Sulamina Chocolate. These findings suggest that implementing competitive pricing, strengthening word of mouth, and enhancing brand image can effectively increase consumer purchasing decisions toward sulamina chocolate products.